Sula - Morrison, Toni (Random House Audio, 2002)
At the heart of Sula is a bond between to women, a friendship whose intensity first sustains, then injuries. Sula and Nel are both black, both smart, and both poor. Through their girlhood years, they share everything. All this changes when Sula gets out of the Bottom, the hilltop neighborhood where there hides a fierce resentment at the invisible line that cannot be overstepped.